The relationship of parenting styles with self-concepts of children with mild mental retardation in selected special schools in Metro Manila - Ni, Jin-Xi (Jessie) (Animo Repository, 2005)
This study attempted to investigate and identify the dominant parenting styles and the levels of self-concept of the children with mild mental retardation from selected public and private schools in Metro Manila. The method of research was descriptive correlational where 58 parents from the public schools and 19 parents from the private schools participated. The number of children participants was the same as the number of parent respondents. To achieve the goals set by the study, the researcher administered a validated questionnaire that enabled the parents to identify their predominant parenting styles (DiGuilio, 1980). Another questionnaire was used to assess the level of the self-concept (Pasao, 2001) of the children with mild mental retardation through the assistance of their teachers and researcher. Findings indicated that the dominant parenting style employed by parents to the MMR in the special schools is the child-style parent (29.87%). On the other hand, out of the 82 MMR respondents, the level of self-concept that receives the highest percentage is average (27.27%). Out of the 77MMR respondents, 53.25% have self-concept lower than average le vel. It means that the self-concept of children with MMR is low. The study showed that there is a significant positive relationship between parenting styles used by parents and the level of self-concept of their children with mild mental retardation, (r=0.74, p<0.01).